Testing of Cbr Subgrade Laboratory Laboratory Using Test Modification Testing Conditions - Lisdayanti, Celestia; Setyanto, Setyanto; Purwadi, Ofik Taufik (Universitas Lampung, 2020)
In the implementation of building construction, the main thing to consider is soil material. Based on that assumptions, soil has a role as a construction material and as a placement of construction.. Therefore, one of the examination processes to discover the soil bearing capacity is California Bearing Ratio (CBR) testing. Compaction in the testing has been done within heavy vehicle pressure on field with the amounts; 2.7 MPa,7 MPa, and 8.4 MPa and the soil sample is from Tirtayasa Area, Sukabumi, Bandar Lampung.The result testing in laboratory had been showed that the soils were classified into A-2-7 soil group that was silty sand type. CBR value without soaking process within modified proctor was 9% and for soaking condition soil was 4.2%. Modified laboratory CBR values of without-soaking condition every pressure were 5.5%, 9.4%, and 9.9%, whereas for the soaking condition were 0.77%, 2.6.5, and 3.3%. In conclusion, the values of CBR are increase as the additions of the pressure given.keywords:heavyvehicle, modifiedpressure’s tool, modified CBR laboratorytest.